EFFECT OF MACROECONOMIC FACTORS ON BOND PRICES: A SURVEY OF BONDS LISTED AT THE NAIROBI SECURITIES EXCHANGE - Ngaruiya, Margaret; Njuguna, Dr. Amos (American Journal of Economics, 2017)
Purpose: The purpose of this study was to establish the effect of macroeconomic factors on bond price. Methodology: The research used an explanatory research design. 65 bonds listed in 23 categories at the NSE. The study used secondary data collected from NSE and the (KNBS) Kenya National Bureau of Statistics. A sample of 10 bonds was selected as these bonds were issued in the January 2008 and were still not mature by the 31st December 2012. Standard deviations were calculated for all the variables in the study. Further statistical analysis was carried out by use of correlation and regression analysis where bond prices were regressed against inflation, exchange rates and economic growth measured using the Kenya's Gross Domestic Product growth. The Statistical Package for Social Sciences (SPSS) version 17 was used to conduct the analysis. The findings were presented in form of tables and figures. Results: The study concluded that inflation had negative and significant relationship on the bond prices. It was also possible to conclude that there was a positive and insignificant relationship between exchange rate and the bond price. The study also concluded that there was a positive and insignificant relationship between GDP and the bond price Unique contribution to theory, practice and policy: This study recommends that investors who are looking to buy into bonds should factor in inflation as this determines the bond prices. It is recommended that economic growth should be enhanced through the pursuit of expansionary monetary and fiscal policies. The study also recommends that investors should also consider factors such as exchange rate as this determines the bond prices. It is recommended that the monetary authority should use policies aimed at weakening the Kenya shilling as doing so would increase bond prices. This is because bond prices would be cheaper and more attractive to foreign investors.